One-pot Hydrothermal Synthesis and Characterization of Zirconium Oxide Nanoparticles - Suresh Sagadevan; Jayasingh Anita Lett; Is Fatimah (Science and Technology Indonesia, 2023)
Zirconia (also known as zirconium dioxide, ZrO2) is a white crystalline naturally occurring mineral that offers excellent optical, dielectric, and mechanical properties. Considering these properties and referring to previous studies on the optimization of ZrO2 NPs synthesis, in the present study, we studied the crystalline, optical, and fluorescence properties of ZrO2 nanoparticles (NPs) formed by the hydrothermal synthesis route. The physicochemical features of the nanoparticles were examined in the photocatalytic oxidation of rhodamine B. From the powder XRD analysis, the ZrO2 NPs were found to be highly crystalline, while the fluorescence (FL) spectra indicated an emission band at 473 nm, which could be linked to a blue shift. Also, the FTIR and Raman spectroscopies confirmed the functionality and bonding, and in addition, the XPS analysis provided the elemental peaks of Zr 3d and O 1s, where all these analyses evidenced the successful formation of ZrO2. Examination of the photocatalytic activity of ZrO2 NPs revealed the capability of the material for rhodamine B photocatalytic degradation effectively, with a degradation efficiency of 86% after 2 h of treatment. Moreover, the nanoparticles exhibited stability and reusability over five cycles. Overall, from the analysis, ZrO2 NPs can be easily formed via the hydrothermal route with tailored optical and fluorescence properties to find applications in the electronics industry for the manufacturing of light emitting devices.